Legal Protection for Consumers and Brand Owners Against the Circulation of Counterfeit Goods: A Case Study of Djitoe Bold Cigarettes in Pangkalpinang - Permatasari, Wulan; Saliman, Abdul Rasyid (International Journal of Science and Society, 2025)
For both registered trademark owners and consumers, the market's circulation of fake goods especially cigarettes under the DJITOE BOLD brand presents significant challenges. The purpose of this study is to examine the types of legal protection available to registered trademark owners who have been harmed by trademark counterfeiting, as well as to consumers who have been harmed by buying subpar counterfeit goods. With a statutory approach and a case study methodology, this study uses a normative legal research type and focuses on Pangkalpinang District Court Decision Number 17/Pid.B/2022/PN Pgp. The results of the study show that while Law Number 8 of 1999 concerning Consumer Protection provides consumer protection, Law Number 20 of 2016 concerning Trademarks and Geographical Indications regulates legal protection for trademark owners. Although the court ruling against the trademark counterfeiter is thought to have satisfied the criminal requirements, consumer protection is still not being implemented as well as it could be, particularly in terms of redress or compensation procedures. To stop the more efficient spread of fake goods in the future, this study suggests that consumer protection organizations, brand owners, and law enforcement organizations coordinate more closely.